PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER MODEL TUTORIAL INTERAKTIF UNTUK SMP/MTS KELAS VII SEMESTER II MATERI SEGIEMPAT - Saputra, Andespa; Yuanita, Putri; Roza, Yenita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research aimed to develop computer-based mathematics learning media model are valid to help students to understand the topic of rectangular.This research and development use development model by Borg and Gall modified by Sugiyono. The steps of this research and development are find the potentials and problems that must to do analyzed first. And then, find the informations by study of literature. Product design is through two stages, that are make paper based design first and then computer based. The programs that used for product design of computer based are program frontpage, microsoft power point and photoshop. Learning media is validated by three experts or validators and further revised based on the input from validators. The revised learning media is tested on two stages, that are a small group consist of five students of class VII and a large group consist of forty students from SMPN 4 Pekanbaru. Based on the analysis of data and discussion can be concluded that computer-based mathematics learning media is already valid with an average value of 3.17 by materials validator and 3.18 by media validator. This computer-based mathematics learning media is also already qualified practicalities with an average of 97,92% on a small test group and 99,22% in the large group test. Key Words : Computer-based Learning Media, Development, Rectangular